Organizational Identity and Paradox: An Analysis of the "Stable State of Instability" of Wikipedia's Identity. (April 2015) - Kozica, Arjan M. F.; Gebhardt, Christian; Müller-Seitz, Gordon; Kaiser, Stephan
Previous studies have reported changes in organizational identities as a result of external or internal triggers. In contrast, we highlight how the paradoxical nature of an organizational identity can influence stability and change that identity. Using the example of Wikipedia, the free online encyclopedia, we show how a "stable state of instability" of the organization's collective identity is constantly being reproduced. We contribute to the literature on organizational identity by first analyzing a case in which identity change is not triggered by a disruptive event. Second, we show how the paradoxical nature of identity triggers attempts to reconcile contradictions of the paradox, culminating in permanent state of gradual changes of organizational identity. Finally, we exemplify how, as a form of partial organization where volunteers take part in the identity formation process, Wikipedia copes with the tensions that ensue from its collective identity.